Carer burden: Associations with attachment, self-efficacy, and care-seeking. (May 2022) - Romano, Daniel; Karantzas, Gery C.; Marshall, Emma M.; Simpson, Jeffry A.; Feeney, Judith A.; McCabe, Marita P.; Lee, Juwon; Mullins, Ellie R.
Familial caregiving research is yet to examine the factors that underpin the association between attachment insecurity and carer burden. Furthermore, previous research consists largely of data collected at a single point in time. This paper addresses these gaps by reporting on a study involving 57 parent–child dyads to determine whether adult children's caregiving self-efficacy mediates the association between carer attachment insecurity and carer burden. Furthermore, care-recipient care-seeking style was investigated as a moderator of the association between carer's attachment insecurity and their self-efficacy. Carers completed self-report measures of attachment orientations at baseline, caregiving self-efficacy at 3 months, and carer burden at 6 months. At 3 months, dyads also engaged in a video-recorded caregiving discussion task assessing care-recipient's observed care-seeking style. The mediation effects of carer attachment orientations on burden through caregiving self-efficacy were contingent on care-recipient indirect-constructive care-seeking. Findings highlight the complex interplay between carer attachment orientations, caregiving self-efficacy, and care-recipient care-seeking style in predicting the burden experienced by adult children.